(untitled) (Revista Electrónica Calidad en la Educación Superior, 2021)
The present work focused on assessing the functions and interrelationships of the mediator and the student in the context of pandemic involvement in the School of Agricultural and Veterinary Sciences of UNAN León, with the purpose of suggesting strategies and conceptual elements in the virtual learning environment (VLE), useful to the teacher and student. The meaningful learning methodology, the participatory action methodology approach, was used. The results show the importance of developing ICT skills in teachers and students and improving the administrative technical conditions of the virtual environment, as well as developing innovation in mediators to transmit quality knowledge in pedagogical processes.